(untitled) (Medical Forum Monthly, 2024)
Objective: To report the effect of seasonal variation in a large cohort that are clinically diagnosed with GBS in tertiary care hospital which will serve as reference for region of Pakistan. Study Design: Retrospective / cross-sectional study Place and Duration of Study: This study was conducted at the Neurology Department, Mayo Hospital Lahore in collaboration with various private and public hospitals in Punjab from March 2013 to February 2015. Materials and Methods: The Inclusion criteria was proven cases of GBS diagnosed according to the Ashbury et al. criteria for GBS based on clinical and electrophysiological findings requiring plasmapharesis. Exclusion criteria included patients of neuropathies associated with chronic inflammatory demyelination (CIDP), diabetes, and other metabolic, toxic and vasculitic neuropathies. A Performa containing demographic, clinical, CSF analysis and electrophysiological detail was designed which was filled by treating physician before requesting for plasmapheresis. The data was analyzed using SPSS version 17. Results: A total of 185 patients were included in the study with 112(60.5%) males and 73(39.5%) females and M: F ratio of 1.53: 1. The mean age was 35.24(SD 15.51) with a range from 11-78 years. Ninety nine (53.5%) cases presented between 20- 40 years of age. The highest incidence of GBS (n=86, 46.5%) was seen during winter season (Dec - Feb), followed by 36(19.5%) in spring (March - May), 46 (24.9%) in rainy summer (June - Sept) or southwest monsoon period and only 17(9.2%) in post monsoon (Oct- Nov). Conclusion: The present study provides data suggesting that there is significant (p=.000) seasonal variation in frequency of GBS patients with the highest frequency observed in winter. The study supports the finding GBS being more common in males as compared to females